(untitled) (International Seven Journal of Health Research, 2024)
Obesity has been treated as a worldwide epidemic, and the number of obese people in Brazilian cities is growing. In most cases, obesity is related to eating high-calorie foods and a lack of physical activity. Thus, the aim of this study was to portray how green areas in the municipality of Espirito Santo do Pinhal-SP help to reduce numerous diseases, including obesity, which is characterized as a public health problem. A survey of areas in the municipality was carried out, looking at the existence of outdoor gyms, tree vegetation and structures for practicing physical activities. During the survey, five green areas used by the population for physical activity were inspected, and it was observed that the places that had walking trails, courts and outdoor gyms were more frequented by the population than the places that only had outdoor gyms. Thus, green areas have a positive impact on people’s lives, encouraging physical activity and greater social interaction, as well as reducing cases of obesity and other cardiovascular comorbidities.